Comparative Evaluation of Oat Hay and Silage Based Rations on Nutrient Utilization and Methane Emissions in Murrah Buffaloes - Sontakke, U B; Prusty, Sonali; Kundu, S S; Sharma, Vijay Kumar (Indian Journal of Animal Nutrition, 2020)
In the present study oat hay and silage were compared for their methane (CH4) production and nutrient utilization potential in Murrah buffaloes. Sixteen dry buffaloes (566.5Â± 12.5kg live weight) were selected from cattle yard of the National Dairy Research Institute, Karnal. Animals were distributed randomly into two groups (T1 and T2) based on body weight. Animals in group T1 and T2 were offered oat hay and oat silage, respectively along with supplementation of mineral mixture and salt. After feeding for a duration of 60 days, a digestibility trial was conducted followed by methane emission measurement by SF6 tracer technique (Johnson et al., 1994). Feed DM intake was similar in both the groups whereas fibre (NDF, ADF) intake was significantly (P